Psychosocial Support in Children Victims of Mount Sinabung Eruption - Marini, Liza; Dalimunthe, Rahma Yurliani; Rangkuti, Rahmi Putri; Siregar, Ade Rahmawati; Daulay, Debby Anggraini; Nasution, Indri Kemala (Journal of Saintech Transfer, 2018)
The eruption of Mount Sinabung in Tanah Karo, North Sumatera, which occurred in November 2013 has caused some people to evacuate to avoid the risk of greater disaster. The eruption produced psychological impacts not only on the parents but also on the children, due to the disruption of life activities, radical life changes and living with other citizens, in unknown length of time. Based on the situation, the Faculty of Psychology, University of Sumatra Utara as part of the USU’s Sinabung Task Force took the initiative to serve the people affected by the eruption of Sinabung, especially the children in the form of Psychosocial Support for Children Victims of Sinabung Eruption activities. The activities performed was psychoeducation and psychological assistance. Psychoeducation assistance was provided in the form of training for trainers (TOT) for 15 people from community cadres in Sinabung, while child psychological assistance was done in the form of trauma healing activity in 250 children in evacuation. This services resulted in cadres and children getting their spirits back to focus on the purpose of life they must achieve with their current limitations, more calm, less stress level, more excited, and feel motivated to go back to life with hope for a better future still exist.